Motivasi Kehadiran Suporter Perempuan Dalam Pertandingan Sepakbola Liga 1 (Indonesian Journal for Physical Education and Sport, 2021)
David Robby Johan. 2020. Motivation of Female Supporters in League Soccer Match 1. Thesis. Department of Physical Education, Health and Recreation, Faculty of Sport Sciences. Semarang State University. Advisor: Andry Akhiruyanto, S.Pd., M.Pd. Keywords: Motivation of Women Supporters, Supporters Groups, Football League 1. Even though there is no special treatment and there are frequent brawls, there are still many female supporters who come to watch football matches in league 1.The aim of the study is to determine the motivation that encourages female supporters to support football clubs in league 1 matches. The method used is a qualitative method by checking the validity of the data using triangulation, collecting data in the form of observation, interviews, and documentation. Observations in order to get an initial description of the research, interviews with eighty-three informants, fifty-seven main informants, twenty-one supporting informants and five as triangulation informants, documentation in the form of KTA photos. The results showed that the need for security, social needs, need for appreciation and self-actualization needs were met in motivating women to attend competitions, while physiological needs were not met. The most dominant need in motivating women is social needs, because there is a sense of love for the pride club. It can be concluded that from the five aspects of motivation in encouraging women to attend competitions, four were fulfilled, namely the aspects of the need for security, social, respect, and self-actualization. Physiological needs are not included because they are not met. Based on the results of the research, it is hoped that the members of the supporters can improve their social life and take care of each other between fellow supporters groups.